2017
DOI: 10.1371/journal.pntd.0005239
|View full text |Cite
|
Sign up to set email alerts
|

Risk mapping of clonorchiasis in the People’s Republic of China: A systematic review and Bayesian geostatistical analysis

Abstract: BackgroundClonorchiasis, one of the most important food-borne trematodiases, affects more than 12 million people in the People’s Republic of China (P.R. China). Spatially explicit risk estimates of Clonorchis sinensis infection are needed in order to target control interventions.MethodologyGeoreferenced survey data pertaining to infection prevalence of C. sinensis in P.R. China from 2000 onwards were obtained via a systematic review in PubMed, ISI Web of Science, Chinese National Knowledge Internet, and Wanfan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Zhou et al . 11 reported that the trend of infection risk is increasing from 2005 onwards and resulted in a threat to the public health in epidemic regions 12 , 13 . Specially, they estimated that around 14.8 million people in China were infected with C .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al . 11 reported that the trend of infection risk is increasing from 2005 onwards and resulted in a threat to the public health in epidemic regions 12 , 13 . Specially, they estimated that around 14.8 million people in China were infected with C .…”
Section: Introductionmentioning
confidence: 99%
“…Specially, they estimated that around 14.8 million people in China were infected with C . sinensis in 2010 11 and there are two major endemic regions in China: provinces in the northeast such as Heilongjiang and Jilin; and provinces in the southeast including Guangdong and Guangxi 8 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a practical example, we applied the model in Fusha Town (coordinates: 22˚40'2.64''N, 113˚20'58.2''E, area: 37 km 2 , and population: 59,593 in the year 2017), located at the northern part of Zhongshan City, Guangdong Province (S1 Fig), where C. sinensis infection is highly endemic [5]. Situated among the Pearl River Delta's vast water network, the town is crisscrossed by rivers and the fishing industry is flourishing.…”
Section: Datamentioning
confidence: 99%
“…The life cycle of C. sinensis involves snails as the first intermediate hosts, fish or shrimp as the second, and humans or other piscivorous mammals as the definitive hosts [5]. The most common way of human getting infected with metacercariae of C. sinensis is eating the raw or insufficiently cooked infected fish/shrimp, the frequency and intensity of which can directly influence the probability of getting infection [6].…”
Section: Introductionmentioning
confidence: 99%